2015
DOI: 10.1177/1024529415611265
|View full text |Cite
|
Sign up to set email alerts
|

Social upgrading in developing country industrial clusters: A reflection on the literature

Abstract: In this article, we examine the role of social upgrading in developing country industrial clusters. We argue that while economic growth and productivity enhancement matter, social conditions within clusters are influenced by state monetary, fiscal, and labour policies and regulations, as well as by dynamic processes of agency among cluster governance actors. We find that the state's policies and regulations might enable or constrain cluster actors to behave in ways that affect social upgrading or downgrading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…These disadvantages render exporting of cluster products more difficult as these products become less competitive (i.e., more expensive) in comparison to regional rivals First, our findings confirmed that clusters do not exist in isolation, but they are rooted in communities (Pyke & Lund-Thomsen, 2016 (Oliver et al, 2017). However, our study has not only focused on the intra-cluster communications (within the cluster), but also stressed the relevance of the inter-cluster communication (i.e., beyond the cluster boundaries).…”
Section: The Global Competitionsupporting
confidence: 75%
“…These disadvantages render exporting of cluster products more difficult as these products become less competitive (i.e., more expensive) in comparison to regional rivals First, our findings confirmed that clusters do not exist in isolation, but they are rooted in communities (Pyke & Lund-Thomsen, 2016 (Oliver et al, 2017). However, our study has not only focused on the intra-cluster communications (within the cluster), but also stressed the relevance of the inter-cluster communication (i.e., beyond the cluster boundaries).…”
Section: The Global Competitionsupporting
confidence: 75%
“…Moreover, Parker (2010) points out that industrial clusters are subject to constant evolution. In this way, Pyke and Lund-Thomsen (2016) argue that social conditions within clusters are influenced by state monetary, fiscal, and labor policies and regulations, as well as by dynamic processes of agency among cluster governance actors. As such, industrial clusters are affected by cluster-specific business environment conditions resulting from individual actions as well as cooperation of companies, government agencies, universities, and other institutions in the national and regional innovation system (Freeman, 1995).…”
Section: Industrial Clustersmentioning
confidence: 99%
“…The literature has recognized the importance of clustering for economic development (Van Dijk and Rabellotti, 1997; Schmitz and Nadvi, 1999). Several contributions in this field showed how clustering in the developing world is often related to (technological or sectoral) upgrading through insertion into broader production structures, also theorized as global commodity or value chains (Bair and Gereffi, 2001; Humphrey and Schmitz, 2002; Sturgeon et al , 2008; Pyke and Lund-Thomsen, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Clusters face various challenges that are critical to their competitiveness (Gereffi and Lee, 2016), such as lack of trust (Chen et al , 2017; Vanzettine et al , 2017), lack of specialized human resources (Pyke and Lund-Thomsen, 2016), lack of information that is critical to business, restrictive government rules and regulations, market access constraints, limited logistical facilities, poor R&D infrastructures (Richardson, 2013), inability to conform with new global standards (Lei and Huang, 2014) and weak links with supporting/related industries (Knorringa and Nadvi, 2016). Challenges that are considered to be at the cluster-level tend to require long-term solutions and concerted efforts to overcome them (Ponte and Sturgeon, 2014; Abdin and Rahman, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation